Global loss of climatically suitable areas for durum wheat growth in the future. (19th October 2021) - Ceglar, Andrej; Toreti, Andrea; Zampieri, Matteo; Royo, Conxita
Abstract: Durum wheat ( Triticum durum Desf.) is a minor cereal crop of key importance for making pasta, couscous, burghul, puddings, bread and many other traditional foods, due to its physical and chemical characteristics. The global demand for high-quality food made of durum wheat has been increasing, which poses a challenge in the face of climate change. Major share of durum wheat production is currently located in semi-arid climates, where the risk of climate extremes such as drought and heat stress will likely substantially increase in the future. To provide a first estimate of future global arable land climatically suitable for growing durum wheat, we develop a suitability model based on support vector machines. The current total share of global arable land climatically suitable to grow rainfed durum wheat is around 13%. Climate change may decrease the suitable area by 19% at mid-century and by 48% at the end of the century. Widespread loss of suitable areas is foreseen in the Mediterranean regions and northern America. On the other hand, climate may become suitable to grow durum wheat in many regions of central and western Europe, while the largest gain in suitability is estimated in some parts of Russia. The overall net loss of suitable areas requires the development and the future adoption of effective and sustainable strategies to stabilize production and adapt the entire food supply chain. Our study also clearly demonstrates the importance of limiting global warming to levels well below 2 °C at the end of the century, which would substantially limit the loss of climatically suitable areas.